Earnings-related parental leave benefits and subjective well-being of young mothers: Evidence from a German parental leave reform - Miriam Maeder (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
This study investigates the causal effect of earnings-related parental leave benefits (Elterngeld) on subjective well-being of young mothers. The new subsidy was introduced in 2007, and replaced a former means-tested benefit (Erziehungsgeld). The reform changed the total amount of benefits as well as the duration of pay. By construction of the reform, the change in benefits differs across population subgroups, depending on their eligibility for the former means-tested benefit. The reform also introduced incentives for paternal leave taking. Income effects, fathers' involvement, and social norms constitute potential channels through which the reform affects well-being. Using a regression discontinuity design, I find remarkable heterogeneities in the response to the reform. While subjective well-being ofWest German mothers increases, East German mothers experience decreasing life satisfaction.
Keywords: J13; J18; J28; I31; 330; Elterngeld; paid parental leave; well-being; life satisfaction